M-Traﬃc - A Traﬃc Information and Monitoring System for Mobile Devices - Romão, Teresa (2006)
This paper presents Mobile Traﬃc (M-Traﬃc), a multiplat- form online traﬃc information system, which provides real time traﬃc information based on image processing, sensor’s data and traveller be- haviour models. In order to estimate route delay and feed the optimal routing algorithm a traﬃc microscopic simulation model is developed and simulation results are presented. This mobile information service ubiqui- tously provides users with traﬃc information regarding their needs and preferences, according to an alert system, which allows a personalised pre-deﬁnition of warning messages.